Coaching research in Gaelic games: a scoping review - Gavin, K.; MacNamara, Á.; Behan, S.; Horgan, P.; Taylor, J. (Sports Coaching Review, 2024)
Gaelic games are central to cultural life in Ireland. As a means of enhancing research-informed practice and future research directions, the aim of this scoping review was to provide a broad overview of the existing literature pertaining to coaching in Gaelic games. Adhering to the Joanna Briggs Institute`s framework, a search of six electronic databases was undertaken. A total of 38 studies met the eligibility criteria and were classified according to four knowledge domains: the player, the sport, pedagogy, and the coaching context. The findings indicated a relative paucity of research across the knowledge domains and the predominance of single-focus studies, highlighting the need for interdisciplinary research. Additionally, limited research methodology, participant samples, and clarity in describing participants were identified as limiting factors. These findings have implications for the broader sport coaching literature, suggesting the need for more comprehensive research across knowledge domains and a focus on practical coaching needs.